The Role of E-Marketing Mix, Influencer, and Followers Engagement Toward Product Purchasing Decisions - Sugiarto, Indra; Simanjuntak, Megawati; Hasanah, Nur (Jurnal Aplikasi Bisnis dan Manajemen, 2022)
Instagram is prevalent in today's digital society, so it is increasingly used as a business marketing media. This research was conducted to explain the internal role of marketers represented by influencers, interaction activities on social media characterized by engagement, and the digital marketing mix approach. The design of this study was a quantitative and cross-sectional study to analyze various variables in the study. The sample was determined using purposive sampling method with 320 respondents participated in this study. Google Form was used to collect data which then analyzed descriptively using Structural Equation Modeling (SEM). This research concluded that influencers significantly affect engagement and purchasing decisions. Moreover, convenience and engagement have a significant effect on purchasing decisions. However, cost has no significant effect on purchasing decisions. Therefore, THE influencer should focus on producing content consistently attractive that is needed by their target market; maintaining convenience, especially in terms of availability, security, and speed in the purchasing process; and periodically measure the engagement rate (ER) as an evaluation material while conveying digital marketing. Influencers also need to keep their attention on social media to improve product purchasing decisions in the future. Keywords: convenience, engagement, influencer, purchasing decision